THE ROLE OF BRAND TRUST IN MEDIATING THE INFLUENCE OF E-WOM ON THE PURCHASE DECISION OF CULOT PANTS BY TEENAGERS IN CANDY PROJECT - Ni Nyoman Triana Prima Dewi; I Made Wardana, Ni Ketut Seminari, Ni Wayan Ekawati (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2024)
This research aims to analyze the role of brand trust in mediating the influence of E-WOM on the decision to purchase culottes at the Candy Project. The population of this research includes consumers who bought culottes at Candy Project with a total of 100 samples. The sample was determined by purposive sampling. Data collection used survey and questionnaire methods which were measured using a 5point Likert scale. Data analysis was carried out using path analysis and the Sobel test. This research shows that E-WOM has significant positive effect on brand trust in culottes in the Candy Project. E-WOM and brand trust significant positive on the decision to purchase culottes at the Candy Project. Brand trust is able to mediate the influence of E-WOM on the decision to purchase culottes at the Candy Project. The practical implications of this research are as consideration and input for Candy Project management in marketing its products in sales to increase product purchases to consumers.